2016
DOI: 10.1016/j.jas.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Tropical ancient DNA from bulk archaeological fish bone reveals the subsistence practices of a historic coastal community in southwest Madagascar

Abstract: Taxonomic identification of archaeological fish bones provides important insights into the subsistence practices of ancient coastal peoples. However, it can be difficult to execute robust morphological identification of fish bones from species-rich fossil assemblages, especially from post-cranial material with few distinguishing features. Fragmentation, weathering and burning further impede taxonomic identification, resulting in large numbers of unidentifiable bones from archaeological sites. This limitation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61). The observation that porous, light fish bones can yield whole genome shotgun libraries with high levels of endogenous DNA underscores our lack of understanding of DNA preservation in different types of animal bone.…”
Section: Discussionsupporting
confidence: 78%
“…Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61). The observation that porous, light fish bones can yield whole genome shotgun libraries with high levels of endogenous DNA underscores our lack of understanding of DNA preservation in different types of animal bone.…”
Section: Discussionsupporting
confidence: 78%
“…The recovery of aDNA or paleoenvironmental DNA from a variety of organisms is a technique that has been greatly improved during the last decade (and now often termed paleogenomics) (Rawlence et al, 2014;Willerslev & Cooper, 2005). The highest success rate for aDNA extraction has been attained with organisms from frozen sites (Gould, León, Buffen, & Thompson, 2010) and generally from dry or cold environments, rather than hot or humid sites (Grealy et al, 2016;Haouchar et al, 2014;Poinar et al, 1998;Rawlence et al, 2014). The Atacama Desert, due to its hyperaridity, therefore offers a potentially perfect environment to preserve aDNA (Kuch et al, 2002), but the high diurnal temperatures and strong radiation could also limit this.…”
Section: Introductionmentioning
confidence: 99%
“…; Grealy et al . ) paired with analyses of fish size that discriminate between juvenile and adult fish (see discussions in Lambrides and Weisler ; Weisler and Green ). Adoption of analytical guidelines that incorporate reliable data on fish ecology and behaviour would also streamline reconstructions and foster appropriate comparison of results between sites.…”
Section: Resultsmentioning
confidence: 99%